2012
DOI: 10.2139/ssrn.2026902
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Environmental Compliance Incentives in U.S. Agriculture: The Role of Commodity, Conservation, and Crop Insurance Programs

Abstract: The U.S. Department of Agriculture (USDA) prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and, where applicable, sex, marital status, familial status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or a part of an individual's income is derived from any public assistance program. (Not all prohibited bases apply to all programs.) Persons with disabilities who require altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…In closing, it is clear that agricultural economic and budgetary factors have weakened Conservation Compliance substantially, and this trend will continue if direct payments are discontinued and compliance is not tied to other farm program benefits such as crop insurance subsidies (Claassen 2012). For critics who have long held that Conservation Compliance policy is not as effective as it could be (Cox et al 2011;Perez 2007;Schnepf 2012), this trend is of deep concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In closing, it is clear that agricultural economic and budgetary factors have weakened Conservation Compliance substantially, and this trend will continue if direct payments are discontinued and compliance is not tied to other farm program benefits such as crop insurance subsidies (Claassen 2012). For critics who have long held that Conservation Compliance policy is not as effective as it could be (Cox et al 2011;Perez 2007;Schnepf 2012), this trend is of deep concern.…”
Section: Discussionmentioning
confidence: 99%
“…Federally subsidized crop insurance has come to represent a substantial proportion of farm program benefits (White and Hoppe 2012), but it is not part of the Conservation Compliance equation. If direct payments are eliminated, farmer incentives to retain conservation practices on HEL will be substantially reduced (Claassen 2012).…”
mentioning
confidence: 99%
“…In the USA, it has been reported that no-till practices resulted in reduction of cropland erosion by more than onethird (from 3.1 billion tonnes of soil to 1.9 billion tonnes) between 1982 and 1997 (Claassen, 2012). In the submontaneous tract of Punjab, India, Bhatt and Khera (2006) reported that runoff and soil loss were 5% and 40% higher under CT compared with MT.…”
Section: Soil Environmentmentioning
confidence: 99%
“…Another possibility for policy innovation would be in the Conservation Title of the next US Farm Bill, scheduled for 2018. In the past, ‘compliance’ programs have required farmers to adopt conservation practices on working lands (to protect wetlands or reduce soil erosion) as a condition for access to crop insurance or other USDA program payments . In principle, similar compliance provisions could be applied to require growers to adopt certain resistance management practices in order to qualify for crop insurance or other USDA programs .…”
Section: Taking Action On the Long‐tailed Risk Of Herbicide Obsolescencementioning
confidence: 99%